Hybrid DSS for recommendations of halal culinary tourism West Sumatra - Mardison Mardison; Agung Ramadhanu; Larissa Navia Rani; Sofika Enggari (Institute of Advanced Engineering and Science, 2021)
Decision support system (DSS) is a system that design to support managers in deciding on multiple criteria and multiple attributes. This study combines two methods in the DSS, that are analytical hierarchy process (AHP) method and simple additive weighting (SAW) method. This combination of two DSS method named hybrid DSS. The AHP method is using to find the weighting or priorities of criteria in DSS and then the value will use by SAW method using to find the decision. The decision of this DSS is the recommendation of halal culinary tourism in West Sumatra Indonesia. The purpose of this study is to provide updates from previous studies, related to adding indicators of halal culinary tourism and other information updates. The number of potential culinary tourism attractions and tourism, the problems that exist in the real field, is still lack of culinary information in West Sumatra. As a result, many tourists find it difficult to find the best and economical culinary. The SAW and AHP methods become the hybrid DSS method that will be able to classify and provide information on halal tourism in West Sumatra that is precise, accurate, consistent, and validated.